1999
DOI: 10.1111/j.1744-7348.1999.tb05265.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infection time and moisture on development of ear blight and deoxynivalenol production by Fusarium spp. in wheat

Abstract: Wheat ears were inoculated with conidia of Fusarium spp. at different growth stages between ear emergence and harvest and moist conditions were maintained for up to 7 days subsequently by mist irrigation. Of the fungi tested (Fusarium culmorum, F. avenaceum, F. tricinctum, F. sporotrichioides and Microdochium nivale), only F. culmorum produced ear blight symptoms and grain samples were found subsequently to contain deoxynivalenol. Most ear infection and deoxynivalenol formation occurred following inoculation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 14 publications
3
70
0
2
Order By: Relevance
“…Current methods of quantifying FHB pathogens include (i) visual assessment of disease severity (20), (ii) counts of infected ears (23) or spikelets (17) at postanthesis, and (iii) counts of fusarium-damaged (22) or -infected (20) kernels at harvest. These techniques estimate pathogen populations indirectly based on disease expression or, in the case of plate counts, directly based on the incidence of the FHB pathogens.…”
mentioning
confidence: 99%
“…Current methods of quantifying FHB pathogens include (i) visual assessment of disease severity (20), (ii) counts of infected ears (23) or spikelets (17) at postanthesis, and (iii) counts of fusarium-damaged (22) or -infected (20) kernels at harvest. These techniques estimate pathogen populations indirectly based on disease expression or, in the case of plate counts, directly based on the incidence of the FHB pathogens.…”
mentioning
confidence: 99%
“…According to Waśkiewicz et al (9), Zhang et al (56), and Ji et al (57), mycotoxin content in grain positively correlates with the severity of FHB. By contrast, Lacey et al (58) reported the presence of DON in grain with no macroscopic symptoms of FHB or grain colonisation by Fusarium spp. These controversial findings could result from differences in infection severity, different plant development stages, and different grain harvest methods (59)(60).…”
Section: Coefficients Of Correlationmentioning
confidence: 91%
“…For example, it has been shown that moisture conditions at anthesis are critical in Fusarium infection of the ears ; while Lacey et al (1999) have shown that Fusarium infection in the UK is exacerbated by wet periods at a critical time in early flowering in the summer, which is the optimum window for susceptibility. Equally, there is evidence that droughed-damaged plants are www.intechopen.com more susceptible to infection, so crop planting should be timed to avoid both high temperature and drought stress during the period of seed development and maturation.…”
Section: Environmental Conditionsmentioning
confidence: 99%